Risk factors of chronic kidney disease among type 2 diabetic patients with longer duration of diabetes - Siddiqui, Khalid; George, Teena P.; Joy, Salini S.; Alfadda, Assim A. (Frontiers in Endocrinology, 2022)
Background Chronic kidney disease (CKD) in patients with type 2 diabetes mellitus (T2DM) is the major cause of end stage renal disease, characterized by proteinuria with a subsequent decline in glomerular filtration rate. Although hyperglycemia is the major risk factor for the development and progression of kidney disease among diabetic patients, many other risk factors also contribute to structural and functional changes in the kidneys. As recommended by Kidney Disease Improving Global Outcomes (KDIGO), CKD classification based on cause and severity links to risk of adverse outcomes including mortality and kidney outcomes. Objective The aim of this study is to investigate the involvement of risk factors associated with the severity of CKD among participants with a longer duration of diabetes. This study also aims to find whether number of risk factors vary among risk of CKD progression categories based on KDIGO classification. Material and methods This cross-sectional study retrospectively selected 424 participants from type 2 diabetic cohort and categorized them based on the classifications for the diagnosis of kidney diseases in patients with diabetes, according to the KDIGO guidelines. Odds ratios and 95% CI of each risk factors according to severity of renal disease were determined. Results Based on the KDIGO classification, participants were categorized into low risk (n=174); moderately increased risk (n=98); and high/very high risk (n=152). Type 2 diabetes (T2D) participants with risk factors such as, hyperlipidemia, hypertension, DM duration ≥15 years and diabetic retinopathy showed a high/very high risk of CKD progression when compared with low-risk category. While T2D participants with risk factors such as, lack of exercise, hypertension, and diabetic retinopathy showed a moderately increased risk of CKD progression. In addition, participants with the highest number of risk factors were significantly distributed among high/very high-risk of CKD progression category. Conclusion This study's findings conclude that patients with T2DM with and duration of ≥15 years, hyperlipidemia, hypertension and diabetic retinopathy have an increased prevalence of advanced CKD. In addition to this, an increased number of risk factors could be an indicator of the severity of CKD in T2D.